Effectiveness of Digital Health Interventions on Glycemic Control in Adults with Type 2 Diabetes: A Systematic Review, Network Meta-Analysis, and RE-AIM Implementation Assessment - Gupta, Bhupesh; Gupta, Shivashish; Singh, Rajdeep; Verma, Nikita; Gupta, Kirtika; Goel, Ramita; Mittal, Anshu (National Journal of Community Medicine, 2026)
Background: Type 2 diabetes mellitus affects more than 500 million adults worldwide. Digital health interventions such as SMS, mobile applications, and telemedicine provide scalable approaches to improve glycaemic control. This systematic review and network meta-analysis assessed the effect of these interventions on HbA1c reduction in adults with T2DM compared with usual care. Methods: Following PRISMA-NMA guidelines and PROSPERO registration (CRD420251181626), we searched six databases and grey literature for RCTs from 2010 to 2025. We included 31 RCTs in narrative synthesis and 15 (∼3,500 participants) in pairwise and network meta-analyses using random-effects models. Results: DHIs significantly reduced HbA1c by a pooled mean difference of -0.37%. Subgroup analyses showed SMS interventions achieved the largest reduction (-0.48%), followed by apps (-0.24%), with lower heterogeneity for SMS. Effects attenuated over longer follow-up. Network meta-analysis indicated no significant differences between modalities, though SMS trended superior. RE-AIM assessment revealed strong reach and effectiveness but limited long-term maintenance. Conclusion: DHIs, especially SMS-based approaches, offer modest yet clinically meaningful HbA1c reductions and are scalable adjuncts to type 2 diabetes management, including in resource-limited settings.